Factors Associated with Outcomes at 1 Year in Paediatric Post-nephrectomy Patients for Nephroblastoma at the University Teaching Hospital and Cancer Diseases Hospital in Lusaka, Zambia - Moonde Zachias Muulu; Bruce Bvulani; Patricia Shinondo; Patrick Kaonga (Wolters Kluwer Medknow Publications, 2024)
Background: Nephroblastoma is the most common primary malignant renal tumour of childhood. The survival rates in high-income countries are approximately 90%. However, low-income countries have low survival rates of 20%-50%. This study assessed factors associated with treatment outcomes of children post-nephrectomy for nephroblastoma at the University Teaching Hospital and Cancer Diseases Hospital in Lusaka, Zambia. Materials and Methods: A retrospective observational cohort study was conducted, where all children diagnosed with unilateral Wilms tumour below the age of 16 years who had nephrectomy from July 2016 to June 2019 were enrolled. Sociodemographic, clinical characteristics and treatment outcomes were noted. All data were coded and stored in a tabular format using Microsoft Excel. Statistical software STATA version 13 was used for analysis. Results: Thirty patients were enrolled. The male-to-female ratio was 1:1. The 1-year event-free survival was 46.7%. Treatment abandonment accounted for 36.6% of the participants. 16.7% of the patients had disease progression. No patient had a relapse or died during the 1-year follow-up period. 66.7% had advanced disease stages III and IV. Advancement in age (above 4.3 years), living in a rural environment more than 100 km away from Lusaka and advanced disease stage were all associated with a poor outcome. Conclusions: Factors associated with a poor outcome in this study were advanced age and late presentation.